Fractured Selves and Fragmented Realities: Trauma, Repression and Modes of Healing in Rachel Zadokâ€™s Gem Squash Tokoloshe - Roux, Rowan (WritingThreeSixty, 2018)
In South Africa, there has long been a difficulty in addressing trauma, particularly in a manner which accounts for both western and traditional forms of healing. This article examines Rachel Zadokâ€™s Gem Squash Tokoloshe, an engaging narrative which has not received a wealth of academic criticism, and explores the lasting effects of childhood trauma. Drawing on the findings of Melanie Kleinâ€™s childhood studies as a means to interpret protagonist Faithâ€™s behaviour, which occasionally borders on the schizophrenic, I attempt to provide a viable paradigm for delineating traditional African healing within western clinical terminology. In understanding the role that traditional healers play in South Africa, I draw on Gavin Ivey and Tertia Myersâ€™s study, â€œThe Psychology of Bewitchmentâ€. In their study, Ivey and Myers make extensive use of the Kleinian psychoanalytical model to interpret a more traditional African belief and integrate its manifestations within a western therapeutic understanding. Although the two models appear to be divergent, the integration of two different schools of thought that nevertheless reveal an epistemological congruity in treating ideas as things allows psychotherapists to manage a broad spectrum of patients.